Editor's note - Sebolai, Kabelo (Journal for Language Teaching, 2024)
What distinguishes this issue is that it may be the only one published in South Africa exclusively in African languages, focusing on the teaching of African languages. Throughout this process, we have gained significant insights as we ventured into what may be uncharted territory, and we hope that this issue serves as a trailblazer, paving the way for more works of this nature. The body of literature on African languages and their pedagogical, cultural, and intellectual dimensions is certainly expansive and multifaceted. This compilation of works showcases a variety of scholarly inquiries into the challenges and innovations within African language education, the cultural significance embedded in linguistic practices, and the broader implications of language policies.